Splinting After Ear Reconstruction: A Stepwise and Inexpensive Workflow Protocol. Issue 4 (April 2018) - Vercruysse, Herman; Green, James I.J.; Osman, Gaynor; Harrison, Brigitte; Miyagi, Kana; Bulstrode, Neil W.
Abstract : Background: Long-term postoperative splinting plays a role in the prevention of contracture of the grafted skin after a second-stage ear reconstruction. The scar retraction could lead to an unfavorable aesthetic outcome. Splinting could play a role to overcome or prevent the loss of projection and the obliteration of the sulcus. Material and Methods: We have defined the characteristics of an ideal long-term splint and present a stepwise clinical protocol for the fabrication of an ethylene-vinyl acetate splint. The splint was applied to all patients included in a prospective study on the postoperative splinting regime. Ethylene-vinyl acetate has proved its safety and longevity in dental prosthetics. Conclusions: Patient compliance was optimal, and no allergic reactions, pressure sores, or skin necrosis were reported. The splint is self-retaining and light weight. Because of its transparent color, it can be easily camouflaged. A stepwise clinical protocol for the fabrication of a low-cost patient-specific ear splint is presented. Abstract : Supplemental digital content is available in the text.